The effects of age priming on recalling age positive/negative and consistent/inconsistent behaviors - Knepple, Amy M. (My University, 2009)
Age stereotypes, both positive and negative, are unique because people who hold them will one day become part of that stereotyped group. The current research asked if age priming college students (N = 61) affects their memory for pictorial images of older persons. Participants were randomly assigned to one of three groups (one year from now prime, age 70 prime, and no prime). After writing about the future self (in one year or at the age 70), or simply receiving the instructions (no prime), each participant was shown a series of images depicting stereotypes of older adults, both positive and negative and consistent and inconsistent. Research on priming suggested that having participants think about themselves at age 70 would influence identification with a new in-group (older adults). However, all groups remembered more negative (p < .001) and inconsistent ( p < .001) stereotype pictures of older adults. This may be due to the novelty of the images. The priming of a different age group may also be difficult because college students strongly identify with their roles as young adults. Future research should assess if different types of priming affect memory for age stereotyped behaviors.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science - Psychology, Experimental at The University of Wisconsin-Oshkosh, 2009
Keywords: Old age, Social aspects; Ageism; Stereotype , Psychology; Priming , Psychology